Formal analysis of ubiquitous computing environments through the APEX framework - Silva, José Luís Cardoso (2012)
Ubiquitous computing (ubicomp) systems involve complex interactions between multiple devices and users. This com-plexity makes it difficult to establish whether: (1) observa-tions made about use are truly representative of all possible interactions; (2) desirable characteristics of the system are true in all possible scenarios. To address these issues, tech-niques are needed that support an exhaustive analysis of a system’s design. This paper demonstrates one such exhaus-tive analysis technique that supports the early evaluation of alternative designs for ubiquitous computing environments. The technique combines models of behavior within the environment with a virtual world that allows its simulation. The models support checking of properties based on pat-terns. These patterns help the analyst to generate and verify relevant properties. Where these properties fail then scenar-ios suggested by the failure provide an important aid to redesign. The proposed technique uses APEX, a framework for rapid prototyping of ubiquitous environments based on Petri nets. The approach is illustrated through a smart li-brary example. Its benefits and limitations are discussed.